Fractional Calculus Operator and Certain Applications in Geometric Function Theory - Irmak, Hüseyin; Tuneski, Nikola (Sarajevo Journal of Mathematics, 2024)
Using a operator involving fractional calculus introduced by Owa and Srivastava [8], two novel families: V_δ^α, β( u;γ) and W_δ^α, β(μ;γ) (δ eq 0, α <1, β <1, γ <1, μ≥ 0, u(-1,0)(0,1)) of functions f(z) which are analytic and univalent in the open unit disk U are defined. Moreover some consequences of main results are shown. 2000 Mathematics Subject Classification. 30C45, 30A10, 26A33